What makes Jesus salvific for the Queer Community? A Moltmann-Inspired Essay in Christology - Ford, Jr., Craig A. (Lumen et Vita, 2015)
In what way is Jesus Christ salvific for the queer community in the United States? By ‘queer community’ here, I understand those whose sexual and gender identities stand at variance with the sexed and gendered expectations of heteronormative culture. This presentation is an essay in the area of queer Christology, a relatively underexplored area of Christian theology. The essay begins unashamedly with the rejection of portrayals of Christ that are manifestly not salvific for queer persons, those representations of a Jesus Christ who defends compulsory heterosexuality or, failing that, voluntary lifetime celibacy. It continues with an analysis of two major figures in the development of queer Christology: the first is Robert Goss, who argues that Jesus Christ is salvific for the queer community because Jesus himself was a gay man; and the second is Marcella Althaus-Reid, who argues that Jesus Christ is salvific for the queer community because Christ embodies the symbolic resistance to binary categorization. I argue that while both of these are important elements in a queer Christology, neither are sufficient: Goss’ representation of Christ scandalizes the universality of Christ by mandating a sexual orientation for which we have no credible textual evidence; and Althaus-Reid’s representation of Christ scandalizes the particularity of Christ by rendering his actual historical existence as Jesus of Nazareth completely irrelevant. In place of these I argue that Christ is salvific for the queer community because his particular life exemplifies what the queer community in America has already lived out (as seen in the AIDS crisis) and continues to live out (in striving for ecclesiastical respectability): Jesus shows the way of passionate loving through suffering—a way that, if queer Christians follow it, leads to resurrection, through hope, and reconciliation with others, through love.